miR-99a regulates CD4+ T cell differentiation and attenuates experimental autoimmune encephalomyelitis by mTOR-mediated glycolysis - Yuting Gu (Elsevier, 2021)
Multiple microRNAs exhibit diverse functions to regulate inflammatory and autoimmune diseases. MicroRNA-99a (miR-99a) has been shown to be involved in adipose tissue inflammation and to be downregulated in the inflammatory lesions of autoimmune diseases rheumatoid arthritis and systemic lupus erythematosus. In this study, we found that miR-99a was downregulated in CD4+ T cells from experimental autoimmune encephalomyelitis (EAE) mice, an animal model of multiple sclerosis. Overexpression of miR-99a alleviated EAE development by promoting regulator T cells and inhibiting T helper type 1 (Th1) cell differentiation. Bioinformatics and functional analyses further revealed that the anti-inflammatory effects of miR-99a was attributable to its role in negatively regulating glycolysis reprogramming of CD4+ T cells by targeting the mTOR pathway. Additionally, miR-99a expression was induced by transforming growth factor β (TGF-β) to regulate CD4+ T cell glycolysis and differentiation. Taken together, our results characterize a pivotal role of miR-99a in regulating CD4+ T cell differentiation and glycolysis reprogramming during EAE development, which may indicate that miR-99a is a promising therapeutic target for the amelioration of multiple sclerosis and possibly other autoimmune diseases.